2018
DOI: 10.4195/nse2018.07.0014
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Water Resource Information Sources and Learning Opportunities in the Pacific Northwest

Abstract: Core Ideas This study evaluated how public information sources for water resource information have changed between 2002 and 2017. Three identical survey questions assessed public information sources in 2002, 2007, 2012, and 2017. The Internet was the information source with the greatest increase in public use over this 15‐year period, increasing from 14.8% in 2002 to 63.0% in 2017. Both formal education level and age of respondents affected their preferred information source choice. The American public is ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 7 publications
7
27
0
Order By: Relevance
“…The public considers water resources (both quality and quantity) to be the most important environmental issues in the four Pacific Northwest (PNW) states—Alaska, Idaho, Oregon, and Washington (Dunlap and Scarce, 1991; Mahler et al, 2004, 2005, 2010). These four states heavily utilize this water resource for agriculture (6 million irrigated hectares), commerce, power production, direct human consumption, food processing, and recreation.…”
mentioning
confidence: 99%
“…The public considers water resources (both quality and quantity) to be the most important environmental issues in the four Pacific Northwest (PNW) states—Alaska, Idaho, Oregon, and Washington (Dunlap and Scarce, 1991; Mahler et al, 2004, 2005, 2010). These four states heavily utilize this water resource for agriculture (6 million irrigated hectares), commerce, power production, direct human consumption, food processing, and recreation.…”
mentioning
confidence: 99%
“…The public in the PNW are aware of the high quality and sufficient quantity of their water resource [1,2,3,4,5]. Studies have shown that a significant portion of public are interested in water and that they access water information on the Internet [6].…”
Section: Introductionmentioning
confidence: 99%
“…The public in the PNW are aware of the high quality and sufficient quantity of their water resource [1,2,3,4,5]. Studies have shown that a significant portion of public are interested in water and that they access water information on the Internet [6]. In addition to seeking out water information many individuals have made voluntary lifestyle changes to protect water quality [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Most students entering college in the United States bring with them a set of mores that have been strongly influenced by their parents and high school peers [13,14]. Unfortunately, many of these beliefs are not strongly rooted in science.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, students could base their responses and actions to issues on science rather than bias or simple beliefs. The 18 environmental issues covered in this course are: (1) population growth, (2) food resources, (3) ecology, (4) biodiversity, (5) non-renewable energy resources, (6) renewable energy resources, (7) nuclear energy, (8) water quantity, (9) surface water quality, (10) drinking water quality, (11) outdoor air pollution, (12) indoor air pollution, (13) acid rainfall, (14) ozone depletion, (15) global warming, (16) solid waste disposal, (17) sewage disposal and (18) hazardous waste.…”
Section: Introductionmentioning
confidence: 99%